PENGOLAHAN LIMBAH CAIR TEMPE (WHEY) SECARA BIOLOGIS DENGAN Acetobacter xylinum UNTUK DIJADIKAN NATA DE SOYA - Nurhayati (Fakultas Teknik - Universitas Satya Negara Indonesia, 2024)
Tempe wastewater still contains organic materials such as protein, fat and carbohydrates that are easily rotten, causing an unpleasant odor and damaging the aquatic ecosystem and environmental aesthetics. Tempe liquid waste contains nutrients (protein, carbohydrates, protein) so that it can be used for other production besides nata. The manufacture of nata de soya is nata derived from tempe liquid waste through a fermentation process using Acetobacter xylinum bacteria with concentrations of 100, 125 and 150 ml / l and sucrose concentrations of 100 gr, 150 gr and 200 gr with a fermentation time of 4 weeks. The parameters of nata de soya research analysis are color, texture, pH, thickness and weight. The results of Nata at a sugar concentration of 100 gr / l obtained the highest weight of 61.2 gr / l and at a sugar concentration of 150 gr / l the lowest weight was 66.7 gr / l while the heaviest nata was 181.7 gr / l at a sugar concentration of 150 gr / l. The average pH is the same, namely 3 and the thickness is between 0.5 to 1 cm, the average texture of all treatments is 20% -30% mm / g.sec. The optimal concentration for making nata de soya is at a sucrose concentration of 150 gr / l and an Acetobacter xylinum concentration of 150 ml / l because the results obtained are quite thick, namely a thickness of 1 cm and a weight of 183.8 gr / l.